Staphylococcus aureus and Methicillin resistant Staphylococcus aureus From The Diabetic Ulcer - Leka Lutpiatina; Nisa Nur Agistni Eriana (Medical Laboratory Technology Journal, 2018)
Infections of diabetic ulcers may occur because patients with diabetes mellitus have a weak immune system and the presence of high blood sugar into a strategic place for bacterial growth one of them is Staphylococcus aureus. Increased resistance of Staphylococcus aureus to various antibiotics, causing problems for the treatment of this infection. As by Methicillin-resistant Staphylococcus aureus (MRSA) This study aims to assess the presence of Staphylococcus aureus and Methicillin-resistant Staphylococcus aureus (MRSA) at diabetic ulcer patient at Banjarmasin city hospital. This research uses descriptive observational research type. The study sample was patients with grade 2 and three diabetic ulcers with a total of 30 samples. The result of the research found 14 Staphylococcus aureus bacteria, Staphylococcus epidermidis nine, Staphylococcus saprophyticus two and 5 Gram-negative bacteria. Of the 14 samples of Staphylococcus aureus, there were eight samples of cefoxitin-resistant samples. The conclusion was 47% of Staphylococcus aureus in patients with a diabetic ulcer at Banjarmasin City Hospital. There was a 57% Methicillin-resistant Staphylococcus aureus in the isolated Staphylococcus aureus found. Need further research on the resistance of antibiotics oxacillin and cefoxitin to other Staphylococcus sp bacteria derived from patient diabetic ulcers.